An Azirine Strategy for the Synthesis of Alkyl 4-Amino-5-(trifluoromethyl)-1H-pyrrole-2-carboxylates - Funt, Liya D.; Tomashenko, Olesya A.; Novikov, Mikhail S.; Khlebnikov, Alexander F. (Synthesis, 2018)
1-(3,3,3-Trifluoro-2,2-dihydroxypropyl)pyridin-1-ium bromide serves as a trifluoromethyl-containing building block for the preparation of trifluoromethyl-substituted aminopyrroles based on the 2H-azirine ring expansion strategy. The primary products, 3-aryl-2-(methoxycarbonyl)-4-(pyridin-1-ium-1-yl)-5-(trifluoromethyl)pyrrol-1-ides, can be hydrogenated by H2/PtO2 to form alkyl 3-aryl-4-(piperidin-1-yl)-5-(trifluoromethyl)-1H-pyrrole-2-carboxylates and transformed into alkyl 4-amino-3-aryl-1-methyl-5-(trifluoromethyl)-1H-pyrrole-2-carboxylates via methylation/hydrazinolysis.
Keywords: trifluoromethylpyrrole; aminopyrrole; trifluoromethylated pyridinium ylide; pyridine; piperidine